2014
DOI: 10.1007/s11745-014-3919-2
|View full text |Cite
|
Sign up to set email alerts
|

Tocotrienol Rich Fraction Reverses Age‐Related Deficits in Spatial Learning and Memory in Aged Rats

Abstract: Little is known about the effect of vitamin E on brain function. Therefore, in this study we evaluated the effect of tocotrienol rich fraction (TRF) on behavioral impairment and oxidative stress in aged rats. Thirty-six male Wistar rats (young: 3-months-old; aged: 21-months-old) were treated with either the control (olive oil) or TRF (200 mg/kg) for 3 months. Behavioral studies were performed using the open field test and Morris water maze (MWM) task. Blood was taken for assessment of DNA damage, plasma malond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 37 publications
3
19
0
Order By: Relevance
“…Besides α-T, other members of the vitamin E family, i.e., tocotrienols (natural compounds present in select vegetable oils, as palm oil), have also been reported to rescue age-related deficits in neuroplasticity and cognition. Adult and old rats supplemented for 8 and 3 months, respectively, with a tocotrienol-rich fraction (200 mg/kg/day) displayed higher spatial learning and memory performance, reduced amount and severity of DNA damage, decreased level of oxidative markers such as malondialdehyde, as well as increased levels of antioxidant enzyme activity and brain vitamin E compared with age-matched, non-supplemented controls [133,134]. …”
Section: α-Tocopherol Synaptic Plasticity and Cognitive Functionsmentioning
confidence: 99%
“…Besides α-T, other members of the vitamin E family, i.e., tocotrienols (natural compounds present in select vegetable oils, as palm oil), have also been reported to rescue age-related deficits in neuroplasticity and cognition. Adult and old rats supplemented for 8 and 3 months, respectively, with a tocotrienol-rich fraction (200 mg/kg/day) displayed higher spatial learning and memory performance, reduced amount and severity of DNA damage, decreased level of oxidative markers such as malondialdehyde, as well as increased levels of antioxidant enzyme activity and brain vitamin E compared with age-matched, non-supplemented controls [133,134]. …”
Section: α-Tocopherol Synaptic Plasticity and Cognitive Functionsmentioning
confidence: 99%
“…Long-term supplementation with a tocotrienol-rich fraction (TRF) to AβPP/PS1 transgenic mice expressing amyloid protein precursor attenuated amyloid beta deposition in the brain and improved cognition [43][44][45]. Aged rats supplemented with TRF also showed improved spatial learning and memory and reduced anxiety levels [46].…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin E plays a central role in scavenging peroxyl radical, preventing lipid peroxidation, and protecting polyunsaturated fatty acids (PUFAs) and other cell membranes components and lipoproteins from oxidation by free radicals [68]. Tocotrienols in particular have been shown previously to exert antioxidative effect in in vitro and in vivo studies [69][70][71]. For instance, up to 100 mol/L of ␥tocotrienol concentration protected against hydrogen peroxide (H 2 O 2 )-induced cell death and apoptosis in primary astrocyte cultures [69].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ␣-tocotrienol has been shown to protect neuronal cell from glutamate-induced toxicity primarily by a direct antioxidant action [70]. In an in vivo study, three months supplementation of TRF (200 mg/kg) has been reported to markedly reduce lipid peroxidation, modulate antioxidant enzymes activity and brain arginine metabolism, and also improve memory in aged rats [19,71]. Tocotrienols supplementation has also been reported to improve lipid profiles in chronic hemodialysis patients [72].…”
Section: Discussionmentioning
confidence: 99%